2010
DOI: 10.1177/1059840510391670
|View full text |Cite
|
Sign up to set email alerts
|

Unmet Needs of Children With Special Health Care Needs in a Specialized Day School Setting

Abstract: Children with Special Health Care Needs (CSHCN) represent a significant component of the pediatric population. They often present to schools with multiple and increasingly complex health issues, including medical technology dependency. Their daily variation in health status requires close monitoring and communication among caregivers. Limited research exists regarding parental concerns and communication between health providers, schools, and families. This study identifies the concerns of parents with CSHCN fa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
23
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 15 publications
(23 citation statements)
references
References 20 publications
0
23
0
Order By: Relevance
“…A lack of close collaboration between the school nurse and the student's other educational team members may allow the student's medical needs to interfere with his or her success in learning (Aruda et al., ). Only 20% of participants indicated that they were “always” invited to participate in collaborative team activities.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…A lack of close collaboration between the school nurse and the student's other educational team members may allow the student's medical needs to interfere with his or her success in learning (Aruda et al., ). Only 20% of participants indicated that they were “always” invited to participate in collaborative team activities.…”
Section: Discussionmentioning
confidence: 99%
“…Providing supports and accommodations for this unique population of students will continue to require “balancing complex health care needs and nursing interventions in the classroom setting… in coordination with educators who traditionally structure the classroom setting. The communication and mechanisms required for success in this coordination are still developing” (Aruda et al., , pp. 214–215).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations